1994
DOI: 10.1063/1.112628
|View full text |Cite
|
Sign up to set email alerts
|

Study on photorefractive effect in KTiOPO4 waveguides

Abstract: Photorefractive effects (PRE) in KTiOPO4 channel waveguides were studied at the wavelengths 0.633 and 0.83 μm. The 4 μm-wide waveguides were fabricated by Rb ion exchange on the z-face of the crystals and along the y axis. At 0.633 μm, crystals from one source showed conventional photorefractive response with a saturation index change Δn of 2×10−5, but samples from a different source were not photorefractive. Neither type of crystals displayed photorefractive behavior in response to 0.83 μm light at guided-wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Several authors reported in the past on spatial modulation of a laser beam in KTP. [15][16][17] In those experiments the buildup of a space-charge field and an electro-optic effect in KTP has been identified as the source of refractive index modulation. This photorefractive effect in KTP has been shown to be extremely anisotropic because of the anisotropy in the ionic conductivities along and perpendicular to the z axis of the crystal ͑10 Ϫ8 and 10 Ϫ12 ⍀ Ϫ1 cm Ϫ1 , respectively͒.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors reported in the past on spatial modulation of a laser beam in KTP. [15][16][17] In those experiments the buildup of a space-charge field and an electro-optic effect in KTP has been identified as the source of refractive index modulation. This photorefractive effect in KTP has been shown to be extremely anisotropic because of the anisotropy in the ionic conductivities along and perpendicular to the z axis of the crystal ͑10 Ϫ8 and 10 Ϫ12 ⍀ Ϫ1 cm Ϫ1 , respectively͒.…”
Section: Discussionmentioning
confidence: 99%
“…This photorefractive effect in KTP has been shown to be extremely anisotropic because of the anisotropy in the ionic conductivities along and perpendicular to the z axis of the crystal ͑10 Ϫ8 and 10 Ϫ12 ⍀ Ϫ1 cm Ϫ1 , respectively͒. 15 Moreover, the typical times needed to observe self-induced effects ranged from several minutes 16 to many hours 17 ͑compare with 4 ms observed in Cr:KTP͒. In addition, even at laser powers much higher than those applied in our experiments the refractive index has changed considerably less than in Cr:KTP.…”
Section: Discussionmentioning
confidence: 99%
“…6 Recently it was found that the photorefractive effect ͑PRE͒ is different for two different kinds of KTP crystals. 7 At 0.633 m, crystals from one source have conventional photorefractive response with a saturation index change of 2ϫ10 Ϫ5 , but samples from a different source do not exhibit photorefractive effect. The reason for this difference is not well understood, and impurities might be one of the reasons.…”
Section: Ion-exchanged Fe Doped Ktiopo 4 Optical Waveguidesmentioning
confidence: 99%